A Qualitative Analysis of Sexual Consent among Heavy-drinking College Men. Issue 7 (April 2022) - Orchowski, Lindsay M.; Oesterle, Daniel W.; Moreno, Oswaldo; Yusufov, Miryam; Berkowitz, Alan; Abbey, Antonia; Barnett, Nancy P.; Borsari, Brian
The current study sought to examine how heavy-drinking college men describe communication of sexual interest and sexual consent. Thematic analysis of semi-structured interviews with 12 heavy-drinking college men identified three themes. Themes included: (a) expectations about parties and sexual activity, (b) observing and communicating sexual interest, and (c) communication of sexual consent. Men reported visiting drinking environments to locate women who they assumed would be open to sexual advances. In these environments, sexual interest was inferred indirectly through shared alcohol use. Anticipating token resistance men reported "trying and trying again" to pursue escalating types of sexual activity. Consent was inferred when participants did not hear "no" from a sexual partner, highlighting the importance of continued education on verbal consent in the context of sexual assault prevention programs.